Influence of Bacillus subtilis ANSB060 on growth, digestive enzyme and aflatoxin residue in Yellow River carp fed diets contaminated with aflatoxin B1. (March 2018) - Fan, Yu; Liu, Laiting; Zhao, Lihong; Wang, Xinping; Wang, Dacai; Huang, Churan; Zhang, Jianyun; Ji, Cheng; Ma, Qiugang
Abstract: Aflatoxin B1 (AFB1 ) elicits serious threats to public health due to its widespread occurrence, as well as its teratogenic, carcinogenic and mutagenic effects. This study aimed to evaluate the toxicity of AFB1 and assess the ameliorative efficacy of Bacillus subtilis ANSB060 on aflatoxicosis in Yellow River carp. A total of 750 juvenile Yellow River carp were allocated into five dietary treatments for 60 days. Diet C0 represented for the negative control, diet M0 containing about 50 μg AFB1 /kg diet represented for the positive control, and diet M0.25, M0.5 and M1.0 was diet M0 supplemented with B. subtilis ANSB060 at a dose of 0.25 × 10 9, 0.5 × 10 9 and 1.0 × 10 9 CFU/kg diet, respectively. The results showed that supplementation of strain ANSB060 restored the reduced body weight and enhanced feed conversion ratio of carp induced by AFB1 towards normal. ANSB060 could also relieve the alterations in hepatic morphology, improve digestive enzyme activities of hepatopancreas and intestine, as well as decrease AFB1 residues in carp's hepatopancreas and gonad. It is concluded that ANSB060 has a protective effect in carp with aflatoxicosis, with a promising potential in feed industrial applications. Highlights: AFB1 caused some detrimental effects on Yellow River carp. B. subtilis ANSB060 could detoxify AFB1 -contaminated feed in vivo and relieve AFB1 -induced growth performance suppression. B. subtilis ANSB060 restored AFB1 -induced alterations in hepatic morphology. B. subtilis ANSB060 increased digestive enzyme activities of hepatopancreas and intestine. B. subtilis ANSB060 decreased AFB1 residues in carp's hepatopancreas and gonad.